Penerapan Problem Based Learning Tipe CPS untuk Meningkatkan Kemampuan Pemecahan Masalah Matematika Siswa Sekolah Dasar - Hamdana Hadaming; Andi Ardhila (Pusat Pengembangan Pendidikan dan Bakat Indonesia, 2021)
This study aims to determine the effect of applying the CPS Type Problem Based Learning learning model on solving math problems for fifth-grade students at Bawakaraeng Makassar State Elementary School. The research design used is The One Group Pretest-Posttest Design, which is a research design carried out with an initial test and a final test. The sampling model used is a non-random sampling technique using sampling technique. The population is fifth-grade students of Bawakaraeng Makassar State Elementary School with a research sample of 20 students in class fifth-grade. The research was carried out for 4 meetings. Data collection techniques used were learning outcomes tests to measure students' problem-solving skills before and after participating in learning using the Problem Based Learning CPS learning model, and student activity observation sheets to observe student activities during the learning process. So the results of the study showed that the average score of the pretest (Pretest) was 63 and there were 10 students (50%) who completed it. While the average score of the final test (Posttest) for students' Mathematics learning outcomes is 83.25 and there are 16 students (80%) in the complete category. Based on the results of the study, the application of the CPS Type Problem Based Learning learning model affects solving mathematical problems in fifth-grade students of Bawakaraeng Makassar State Elementary School.